2019
DOI: 10.3390/ijerph16245051
|View full text |Cite
|
Sign up to set email alerts
|

Does Residents’ Satisfaction with the Neighbourhood Environment Relate to Residents’ Self-Rated Health? Evidence from Beijing

Abstract: Objective: The aim of this study is to examine the association between satisfaction with two types of green space and residents' self-rated health by comparing neighbourhood green space (NGS) and community green space (CGS) across spatial dimensions. Method: This study was based on 4291 workers from a large-scale individual survey of inhabitants of Beijing city in 2013. Multilevel ordered logistic regression analysis was used to examine the associations between residents' satisfaction with the two types of gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…This study offers several valuable insights. First, previous research indicated mixed results regarding the correlation between natural environments and self-rated health ( 36 ). Besides Liu et al ( 4 ), our findings provide additional empirical support for the potential mediating role of residents' satisfaction in the relationship between green space and mental health, unveiling that a neighborhood's relative extent of green space can directly improve residents' mental health.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study offers several valuable insights. First, previous research indicated mixed results regarding the correlation between natural environments and self-rated health ( 36 ). Besides Liu et al ( 4 ), our findings provide additional empirical support for the potential mediating role of residents' satisfaction in the relationship between green space and mental health, unveiling that a neighborhood's relative extent of green space can directly improve residents' mental health.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The topic of green space and mental health lends itself to case studies. Accordingly, relevant work has involved American, British, and other European cities (e.g., in Denmark); Australia; and the Chinese cities of Beijing and Guangzhou ( 4 , 6 , 9 , 36 ). Many other parts of the world (e.g., most of Asia, Africa, less affluent European countries, and South America) have not been the subjects of such research.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In further research, it is necessary to analyze the performance connotation of LCP more deeply and construct a richer index system to comprehensively evaluate LCP performance in different modes. Last but not least, as LCPs can effectively promote the management of public space in rural areas and the construction of a green and healthy habitat environment through the methods of production space management, urban, and rural overall development, ecological environment governance, and extensive participation of farmers [55,56], so it may be another important direction for future research to explore the impact mechanism and its coupling relationship on LCP and public space governance to ensure the healthy and stable development of rural areas.…”
Section: Study Limitations and Further Research Prospectsmentioning
confidence: 99%